Discussion4

Discussion4 - Discussion 4 Emily Mower Topics to be covered...

This preview shows pages 1–5. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Discussion 4 Emily Mower February 17, 2010 Topics to be covered: • Survivors guide: pages 6-8 • Description of mixed random variables • Software error vs. maintenance costs • Textbook problem 2.100 1 1 Survivor’s Guide 1.1 Inequalities and Their Graphs The best way to think about how to deal with inequalities is to figure out where the function is zero. Then plug in values on either side of this line to figure out which side to shade. See Figures 1 and 2 for examples. Figure 1: An example of the graphical depiction of inequalities . Figure 2: An example of the graphical depiction of inequalities . 2 1.2 Series Expansions Let’s start with the finite series: a + ar + ar 2 + ... + ar n- 1 • Let s = 1 + r + r 2 + ... + r n- 1 • Thus, rs = r + r 2 + r 3 + ... + r n • Subtract rs from s : s- rs = 1- r n • Rearrange to solve for s: s = 1- r n 1- r • Multiply by a factor, a: as = a- ar n 1- r Thus, for the finite series: a + ar + ar 2 + ... + ar n- 1 we can say: a + ar + ar 2 + ... + ar n- 1 = a- ar n 1- r When a = 1, this simplifies to: 1 + r + r 2 + ... + r n- 1 = 1- r n 1- r Let’s now look at the infinite series: a + ar + ar 2 + ... If | r | < 1 , then as n → ∞ : a + ar + ar 2 + ... = a 1- r , | r | < 1 When a = 1, this simplifies to: 1 + r + r 2 + ... = 1 1- r , | r | < 1 Let’s differentiate the infinite series: 1 + r + r 2 + r 3 + ... D (1 + r + r 2 + r 3 + ... ) = 1 + 2 r + 3 r 2 + r 3 + ... = D ( 1 1- r ) = 1 (1- r ) 2 , | r | < 1 3 Let’s differentiate the finite series: 1 + r + r 2 + r 3 + ... + r n D (1 + r + r 2 + r 3 + ... + r n- 1 ) = 1 + 2 r + 3 r 2 + r 3 + ... + nr n- 2 = D ( 1- x n 1- x ) = nr n- ( n + 1) r n- 1 + 1 (1- r ) 2 Now let’s look at e . In 1683, Johann Bernoulli defined e as: e = lim n →∞ (1 + 1 n ) n e x = lim n →∞ (1 + x n ) n If we want develop an expansion of the e or e x we need to use the binomial theorem....
View Full Document

This note was uploaded on 02/26/2010 for the course EE ? taught by Professor Mendel during the Spring '10 term at USC.

Page1 / 12

Discussion4 - Discussion 4 Emily Mower Topics to be covered...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online